Plasma Cell Gingivitis: A Rare Perpetuating Entity - Anil Agrawal1 , Ayushi Singh2 , Arvind Bhake1 , Sunita Vagha3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Plasma cell gingivitis is a rare unexpected condition in an individual inconsiderate to bediagnosed for. Although many research has shown the light on the treatment and diagnosis of the diseaseagain exclusion criteria are most considerate. In the current situation patient presented with typical featuresof inflammation after the confirmatory histopathological diagnosis only plasma cell gingivitis came intocontemplation. Properly applied medications were provided to the patient and improvement was seen infollow up. Being congruent with a number of conditions, its diagnosis is served quite succour for mankind.Case Presentation: A 35-year-old female presented with swollen and occasional painful gums, withintermittent gum bleeding. Her medical, dental, family history and personal history were non-contributory.There was no history of any allergy or Para functional habits such as mouth breathing. No abnormalitieswere detected in her general physical and extra oral examination. On examination, there was erythema andinflammation of gums suggestive of gingivitis, with normal CBC and PS report. She has been refractedany of the treatment given earlier. Thereafter, a punch biopsy of gums was done and the tissue was sent forhistopathological examination.Conclusion: PCG is a remarkable condition, most likely allergic in nature. While being a purely benign, theclinical appearance and localization may conceal much more detrimental conditions Therefore, each lesionrequires due attention